Influence of short-term aging on anti-cracking performance of warm modified asphalt at intermediate temperature - Liu, Xiang; Li, Bo; Jia, Meng; Zhang, Zhengwei; Liu, Zhuangzhuang; Li, Hongyin (Colloids and surfaces. A, Physicochemical and engineering aspects, 2019)
[Display omitted] The present study was conducted to evaluate the cracking behaviors of warm modified asphalt with different short-term aging levels. To this end, nine types of asphalt binders including three base asphalt and those with two warm mix asphalt (WMA) additives were considered. Thin film oven test (TFOT) with various durations (0h, 5h, 7h) were carried out to simulate different short-term aging levels of the nine types of binders. Based on thermodynamic models of cohesion energy under dry and wet conditions, anti-cracking performances of the warm modified asphalt with various aging levels were evaluated by using contact angle tests. The results show that the cohesion characteristic of asphalt in dry condition is deteriorated after short-term aging, but such deterioration can be delayed with the addition of WMA additives. Short-term aging processes result in anti-cracking improvement of asphalt in the presence of water. The cracking resistance under dry condition is highly correlated to the dispersion component of asphalt, while the cracking resistance under wet condition shows a good relationship with the polar component of asphalt binder.